To factor the polynomial \(16x^8 - 49x^2\), we can recognize that it fits the form of a difference of squares. In general, the difference of squares pattern is given by:
\[ a^2 - b^2 = (a - b)(a + b) \]
We can rewrite the polynomial as follows:
-
Identify \(a\) and \(b\):
- \(a^2 = 16x^8\) implies \(a = 4x^4\) (since \((4x^4)^2 = 16x^8\))
- \(b^2 = 49x^2\) implies \(b = 7x\) (since \((7x)^2 = 49x^2\))
-
Now we can apply the difference of squares pattern: \[ 16x^8 - 49x^2 = (4x^4)^2 - (7x)^2 = (4x^4 - 7x)(4x^4 + 7x) \]
Thus, the answer to the question is: (a−b)(a+b)=a^2−b^2.